MODELLING HOUSEHOLD DEMAND FOR PLANTAIN IN URBAN COMMUNITIES, OYO STATE: A LINEAR APPROXIMATE ALMOST IDEAL DEMAND SYSTEM MODEL (LA-AIDS) APPROACH - Omodara , Olabisi Damilola; Oyebanji, Akinsola Temitope; Olakojo, Tijesunimi Oluwapelumi (Agricultural Socio-Economics Journal, 2024)
The study was conducted to determine household demand for plantain in urban communities of Oyo State, Nigeria. The objectives analyzed the nature of demand for plantain as a consumer good, determined the relationship between plantain and other staples; and identified the determinants of household demand for plantain. A multi-stage sampling procedure was used to select 120 respondents for the study. Primary data was collected with the aid of a structured questionnaire and analyzed using descriptive Statistics and the Linear Approximate Almost Ideal System Model. The descriptive statistics showed that the households have an average age of 29 years with an average household size of 7 members. Most of the respondents have tertiary education degree and earned an average of 90,062.50 per month. Our findings further reveal plantain to be mostly consumed towards the end of the year between September to December due to the large sale of plantain at cheaper prices during this period. This is influenced by peak harvesting seasons across various regions of Nigeria in the rainy seasons, leading to much supply of plantain in the market. The result of the Linear Approximate Almost Ideal System Model (LA-AIDS) showed that the total household expenditure on food, age of respondents, marital status, and total expenditure on commodities like rice, yam, and yam flour determines the demand for plantain among the households. Demand elasticity categorized plantain as a luxury good with inelastic demand in the urban areas of Oyo State. Therefore, price and income generating policies that will enhance the purchasing power of households for plantain should be pursued with the provision of quality price information systems to improve household demand for plantain.